Effect of different approaches to treatment of smoking as a potential confounder in a case–control study on occupational exposures. Issue 2 (18th January 2005) - Richiardi, L; Forastiere, F; Boffetta, P; Simonato, L; Merletti, F
Abstract : Aim: To evaluate the effect of different approaches to treatment of smoking as a potential confounder in an occupational study of lung cancer. Methods: Data were used from a case–control study on 956 men with lung cancer and 1253 population controls recruited in two northern Italian areas during 1990–1992. The risk of lung cancer associated with 11 selected job titles and eight selected industrial activities was estimated using seven different methods to treat smoking history. To evaluate the confounding effect of smoking, odds ratios obtained using the first six models were compared with estimates from the seventh and most complex model, in which cumulative tobacco consumption and time since cessation were considered. Results: Although crude odds ratios for some of the occupational categories were biased by up to 25%, such bias decreased to less than 10% when a simple model including smoking status (never, ex-, current) was used. Conclusions: In occupational studies on lung cancer risk, information on smoking status may allow satisfactory control of the potential confounding effect of the habit.